Study of psychosocial aspects of unmarried pregnancy in a tertiary care hospital - Soundararajan, Pradeeba; Poovathi, Muthuramu (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Unmarried pregnancy is a major health and social problem in many developed as well as developing countries with unique medical and psychosocial consequences for the patient and society. The objective of this study was study the psychosocial aspects of unmarried pregnancy. Methods: Study was done over a period of one year. Data collected from 31 unmarried abortion seekers in a tertiary care Medical College hospital of Tamilnadu. Results: showed a strong association between unmarried adolescent pregnancy and lack of parental supervision and control , poor intra-family relationship , family problem , lack of knowledge on sexual and reproductive health ), and nonengagement of adolescent in any productive activity. Conclusions: Ignorance regarding sexuality and reproduction along with adventurous nature and poor negotiation skills predisposes unmarried girls for early sexual activity that may lead to various problems like unwanted pregnancy and STIs that may cause psycho-social-economic problems for the unmarried girl.